2014
DOI: 10.1111/ajo.12219
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancy amongst women attending antenatal clinics at the Port Moresby General Hospital

Abstract: Unintended pregnancy was common and occurred more frequently amongst women who already had three or more children, often leading to birth spacing of under two years. There is a need for effective programs and strategies to increase access to contraceptive information and services. Immediate provision of long-acting reversible contraceptive methods in the postnatal period could facilitate such access and reduce unplanned pregnancy amongst multiparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 18 publications
12
44
1
Order By: Relevance
“…Recent studies have shown that the majority of pregnancies after short intervals are unintended. [48][49][50] Moreover, unintended pregnancy is associated with a higher risk of prenatal maternal stress. 51,52 Gunnes et al 30 hypothesized that closely spaced pregnancies would be associated with increased maternal stress during the pregnancy of the index child, which increases the likelihood of developing ASD in this child.…”
Section: Main Findingsmentioning
confidence: 99%
“…Recent studies have shown that the majority of pregnancies after short intervals are unintended. [48][49][50] Moreover, unintended pregnancy is associated with a higher risk of prenatal maternal stress. 51,52 Gunnes et al 30 hypothesized that closely spaced pregnancies would be associated with increased maternal stress during the pregnancy of the index child, which increases the likelihood of developing ASD in this child.…”
Section: Main Findingsmentioning
confidence: 99%
“…Misoprostol to end an unwanted pregnancy is becoming increasingly used in both developed and developing countries [4, 8] and has been previously reported in the setting for this study [26]. Table 4.7 outlines correct regimes for the use of misoprostol-only induced abortion.…”
Section: Discussionmentioning
confidence: 99%
“…In 1968, obstetric causes was among the top fifteen leading causes of death in hospital, a ranking that remained unchanged in 1998 [25]. Since 1978, all health workers have been encouraged to report all maternal deaths through Maternal Mortality report forms [26], however in reality such formal documentation is rarely undertaken, and many maternal deaths remain unreported [27][28][29]. In her earlier work in 1990, Gillett [13] noticed the same causes of maternal death as are seen today, that is PPH and sepsis.…”
Section: Causes and Timing Of Maternal Deathsmentioning
confidence: 99%
See 2 more Smart Citations